Work-Life Balance and Its Role in Employee Engagement and Satisfaction - Mayank Pant, Bijesh Dhyani, (European Economic Letters (EEL), 2023)
Employee engagement is declining today, and workers need to be more engaged. During a recession, having an entire team and engaged workers might be the difference between a company's survival and success. The concept and parameters used to measure staff morale are still being determined. However, these structures and metrics need a generally acknowledged definition. In other words, researchers and reviewers sometimes use different aspects and dimensions when describing employee engagement. The workplace of today has undergone significant change. To design strategies or address other context-related concerns that will facilitate complete employee engagement, managers need to have a solid understanding of the anticipated process of employee involvement. The article aims to identify the elements and facets of employee engagement and look at how it affects job satisfaction at an oleo chemical company. The data were analyzed using multiple regression, factor, and reliability analyses. The research questions posed were addressed in this study. Organizational recommendations are reported.